Community Conduct and Its Influence on Forest Fires in the Sebangau Watershed: Spatial Analysis Utilizing Remote Sensing and Community Observation - Perkasa, Petrisly; Aguswan, Yusuf; Syam’ani; Debora; Sitinjak, Tarita Aprilani; Purnawan, Eldy Indra; Ovany, Riska (UIR PRESS, 2026)
The frequent forest fires along the Sebangau River in Central Kalimantan, particularly during the dry season, have emerged as a significant environmental issue, driven by human activities such as the burning of wild pandanus on the riverbanks to facilitate the deployment of fishing equipment. This study examines the correlation between community behavior, particularly among fishermen, and the occurrence of forest fires in the Sebangau watershed, while also investigating the causes of these fires. The research methodology employs a combined approach, using remote sensing analysis (MODIS) to map forest fire patterns spatially, alongside observations from local groups to gather qualitative data on land-burning practices. The study's findings indicated that forest fires along the Sebangau River were predominantly caused by fishermen burning wild pandanus, often leading to uncontrolled spread. The El Niño phenomenon exacerbates drought conditions that instigate fires. This study underscores the significance of a community-oriented strategy for forest fire mitigation and the necessity of sustainable management practices that foster collaboration between governmental entities and communities to reduce the likelihood of future forest fires.